Analytical techniques in polymer chemistry with special reference to urea-formaldehyde resins - Ferg, Ernest Eduard (My University, 1993)
One of the greatest environmental drives in the synthetic resins field has been to decrease the formaldehyde emission from cured urea formaldehyde (UF) resins, without adversely affecting their excellent technical performance. [Abbreviated Abstract. Open document to view full version]
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science (Chemistry) May 1993
Keywords: Urea-formaldehyde resins; Polymers